Nylon-6-Coated Doxorubicin-Loaded Magnetic Nanoparticles and Nanocapsules for Cancer Treatment - Ekaterina Kovrigina; Yuliya Poletaeva; Yanfang Zheng; Alexey Chubarov; Elena Dmitrienko (Magnetochemistry, 2023)
Nanoplatforms used for the loading of anticancer drugs constitute a promising approach to cancer treatment and reducing the side effects of these drugs. Among the cutting-edge systems used in this area are magnetic nanocomposites (MNCs) and nanocapsules (NCs). MNCs are considered to constitute a smart tool for magnetic-field-guided targeted drug delivery, magnetic resonance imaging, and hyperthermia therapy. Nanocapsules offer great potential due to their ability to control drug-loading capacity, their release efficiency, their stability, and the ease with which their surfaces can be modified. This study proposes a method for the development of nylon-6-coated MNCs and nylon-6 polymeric membrane NCs. A biocompatible nylon-6 polymer was first used for NC synthesis. Oleic-acid-modified and non-modified Fe3O4 nanoparticles were synthesized for the production of nylon-coated MNCs. Dynamic light scattering (DLS), transmission electron microscopy (TEM), and ζ-potential measurements were used to perform size, morphology, and charge analyses. The above-mentioned two types of MNCs were considered templates for the manufacture of nylon nanocapsules, leading to NCs with different charges and structures. The developed oleic-acid-coated nylon-6 MNCs and NCs showed excellent loading values of the chemotherapy drug doxorubicin (DOX) of up to 732 and 943 µg/mg (DOX/MNC or NC), respectively. On the contrary, the capacity of the nano-construction that was not modified with oleic acid did not exceed 140 µg/mg. The DOX-loaded nanosystems displayed pH-sensitive drug release properties, for which the highest efficiency was observed at an acidic pH. The series of DOX-loaded MNCs and NCs inhibited A549 and HEK 293FT cell lines, with the lowest IC50 value of 0.31 µM observed for the nanocapsules, which is a 1.5-fold lower concentration than the free DOX. Therefore, the presented nanoscale systems offer great potential for cancer treatment.